Autoregressive Integrated Moving Average Model(Arima)For Forecasting Wind Speed. - A, Shamshad; W. M. A, Wan Hussin; M. A, Bawadi; S. A, Mohd. Sanusi (2003)

(untitled)
For proper planning and efficient utilization of wind energy, wind speed predictions are important. In the present study the hourly wind speed data from 1995 to 2001 at three meteorological stations at a height of 14 m above the ground level have been analysed for fitting autoregressive integrated moving average (ARIMA) models.